On Several Polish Poems From 1829–1870 with Venice in the Background - Berkan-Jabłońska, Maria (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The subject of the article is a review of images of Venice recorded in Polish poetry between the years 1829–1870. The paper deliberately stops in the 1870s in the selection of the literary material to be analysed, focusing on the Romantic and post-Romantic tradition. Due to the different artistic value of the works, the author adopted the formula of a historical and literary “catalogue” ordered chronologically and partly problematicised according to the functions which Venetian scenery or culture perform in them. Attention is drawn to the fact that Venetian motifs present in the poetry of Polish artists tend to be related to particular phenomena and topics, such as Byronism, Gothicism, political and national camouflage, love and existential masks, conflict between people and power. The authors referred to in the paper include, among others, Adam Mickiewicz, Józef Ignacy Kraszewski, Zygmunt Krasiński, Edward Dembowski, Edmund Chojecki, Karol Baliński, Mieczysław Gwalbert Pawlikowski, Teofil Lenartowicz, Feliks Wicherski, Teofil Nowosielski, Aleksander Michaux and Wiktor Gomulicki.